Sample preparation method and analytical test method of cobalt-iron-boron alloy
By using at least two sample preparation methods, composite acids are used to remove contaminants on the surface of cobalt iron-boron alloy, and the problems of low accuracy and long time in glow discharge mass spectrometer detection are solved, and the preparation of clean samples and the acquisition of high accuracy test results are achieved.
Patent Information
- Application Number
- CN202510108642.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-01-23
AI Technical Summary
Cobalt iron-boron alloys have low accuracy and long time due to the presence of surface contaminants in glow discharge mass spectrometer detection. The prior art is difficult to effectively remove contaminants and avoid the introduction of impurities.
The sample preparation method of at least two times is used to remove contaminants on the surface of the cobalt iron-boron alloy by composite acids (combination of nitric acid and hydrofluoric acid), and water and alcohol wash after each time. As the number of picklings increases, the concentration of the pickling agent gradually decreases to avoid excessive corrosion and waste of resources.
Effectively remove contaminants on the surface of cobalt iron-boron alloy and avoid the introduction of impurities. The clean samples prepared are suitable for glow discharge mass spectrometer detection, shortening the test time and improving the accuracy of test results.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of analysis and testing, and relates to a sample preparation method and an analysis and testing method for a cobalt-iron-boron alloy. Background Art
[0002] Cobalt-iron-boron alloy is mainly composed of cobalt (Co), iron (Fe) and boron (B) elements. Among them, cobalt and iron are transition metal elements. Their atomic structure characteristics make the alloy have good magnetic and mechanical properties. The addition of boron can significantly improve the magnetic properties of the alloy. Generally speaking, the purity and impurity elements of cobalt-iron-boron alloy have an important influence on its performance. Therefore, by testing the purity and impurity elements of cobalt-iron-boron alloy, the performance of the alloy can be judged to a certain extent.
[0003] Glow discharge mass spectrometer (GDMS) is a direct solid analysis technology with advantages such as high sensitivity, high resolution, small matrix effect and full element analysis. It is the best means to analyze high-purity metal solid samples. Generally, there are constant element pollutants on the surface of cobalt-iron-boron alloys, such as Al, Si, P, S or Cl elements, which cannot be directly tested by glow discharge mass spectrometry, otherwise it will lead to low accuracy of test results and long test time.
[0004] Therefore, there is an urgent need to provide a method for preparing a sample of a cobalt-iron-boron alloy, wherein the prepared sample is suitable for detection by a glow discharge mass spectrometer, which can shorten the test time and improve the accuracy of the test results. Summary of the invention
[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a sample preparation method and an analytical test method for a cobalt-iron-boron alloy. The sample preparation method of the present invention can effectively remove pollutants on the surface of the cobalt-iron-boron alloy through at least two acid washing steps, and the introduction of impurities is avoided as much as possible during the sample preparation process, thereby successfully preparing a clean sample suitable for detection by a glow discharge mass spectrometer, thereby shortening the test time of the glow discharge mass spectrometer and ensuring that the test results have high accuracy.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a sample of a cobalt-iron-boron alloy, the method comprising:
[0008] The cobalt-iron-boron alloy is pickled at least twice, and then cleaned and dried to obtain a sample to be tested; wherein, as the number of pickling times increases, the concentration of the pickling agent gradually decreases.
[0009] The at least two times may be, for example, 2 times, 3 times, 5 times or 6 times, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0010] The sample preparation method of the present invention can effectively remove pollutants on the surface of the cobalt-iron-boron alloy through at least two acid washing steps, and the introduction of impurities is avoided as much as possible during the sample preparation process, thereby successfully preparing a clean sample to be tested that is suitable for detection by a glow discharge mass spectrometer, thereby shortening the test time of the glow discharge mass spectrometer and ensuring that the test results are highly accurate.
[0011] In the sample preparation method of the present invention, as the number of pickling times increases, the concentration of the pickling agent gradually decreases, which can prevent the cobalt-iron-boron alloy from being excessively corroded and save resources.
[0012] Preferably, the cobalt-iron-boron alloy is in block shape with a size of 20-35mm×20-35mm×10-20mm, for example, 20mm×20mm×10mm, 30mm×30mm×15mm or 35mm×35mm×20mm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0013] Preferably, the solid-to-liquid ratio of the cobalt-iron-boron alloy and the pickling agent is 1g:(3-5)mL, for example, it can be 1g:3mL, 1g:4mL or 1g:5mL, etc., but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] Preferably, the pickling agent used in each pickling is a composite acid, and the composite acid includes nitric acid and hydrofluoric acid.
[0015] Preferably, the mass concentration of nitric acid in the composite acid is 10-20%, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%; the mass concentration of hydrofluoric acid in the composite acid is 10-20%, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, etc., but is not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0016] In the present invention, the combination of nitric acid and hydrofluoric acid can effectively remove pollutants on the surface of the cobalt-iron-boron alloy. During each pickling, when the mass concentrations of nitric acid and hydrofluoric acid meet the above preferred range, the effect of removing pollutants is better.
[0017] Preferably, the mass concentration ratio of nitric acid to hydrofluoric acid in the composite acid is (1-3):(1-3), wherein the selection range of nitric acid (1-3) can be, for example, 1, 2 or 3, etc.; the selection range of hydrofluoric acid (1-3) can be, for example, 1, 2 or 3, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] Preferably, as the number of pickling times increases, the mass concentrations of nitric acid and hydrofluoric acid in the composite acid gradually decrease.
[0019] Preferably, the time range of each pickling is 2-5 minutes, for example, it can be 2 minutes, 3 minutes, 4 minutes or 5 minutes, etc., but it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0020] Preferably, each pickling process is accompanied by ultrasound, and the power range of the ultrasound is 120-180W, for example, it can be 120W, 130W, 140W, 150W, 160W, 170W or 180W, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] Preferably, during the at least two acid washes, a water wash step is performed between two adjacent acid washes.
[0022] Preferably, the cleaning comprises the steps of sequentially performing water washing and alcohol washing.
[0023] Preferably, the reagent used in the alcohol washing includes ethanol.
[0024] Preferably, the water used for each water washing is deionized water or pure water.
[0025] Preferably, a baking lamp is used to dry the material after alcohol washing.
[0026] Preferably, the sample preparation method is carried out in a fume hood.
[0027] In the present invention, the sample preparation process is carried out in a fume hood, the purity of the reagents used is above premium grade, and the water is deionized water or pure water, so as to avoid the introduction of contamination as much as possible.
[0028] In a second aspect, the present invention provides an analysis and testing method for a cobalt-iron-boron alloy, the analysis and testing method comprising:
[0029] The sample to be tested prepared by the sample preparation method described in the first aspect is placed in a glow discharge mass spectrometer, and then cooled and sputtered in sequence to obtain a test result.
[0030] In the present invention, the sample to be tested is prepared by the sample preparation method described in the first aspect, and the pollutants on its surface have been removed as much as possible and the introduction of impurities has been avoided as much as possible, thereby shortening the test analysis time of the glow discharge mass spectrometer and ensuring the accuracy of the data.
[0031] Preferably, the sample to be tested is first loaded into the instrument sample chamber of the glow discharge mass spectrometer, then evacuated, and then pushed into the discharge chamber of the glow discharge mass spectrometer, and then the cooling and sputtering steps are performed in sequence.
[0032] Preferably, the refrigeration time is 10 minutes.
[0033] Preferably, the sputtering voltage is 1-1.1 kV.
[0034] Preferably, the sputtering current is 2-2.2 mA, for example, 2 mA, 2.1 mA or 2.2 mA, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0035] Preferably, the resolution of the glow discharge mass spectrometer is 4000-5000.
[0036] In the present invention, by using the above-mentioned sputtering voltage, current and resolution for testing, a stronger signal with high sensitivity can be obtained.
[0037] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] The sample preparation method of the present invention can effectively remove pollutants on the surface of the cobalt-iron-boron alloy through at least two acid washing steps, and the introduction of impurities is avoided as much as possible during the sample preparation process, thereby successfully preparing a clean sample to be tested that is suitable for detection by a glow discharge mass spectrometer, thereby shortening the test time of the glow discharge mass spectrometer and ensuring that the test results are highly accurate.
[0040] In the sample preparation method of the present invention, as the number of pickling times increases, the concentration of the pickling agent gradually decreases, which can prevent the cobalt-iron-boron alloy from being excessively corroded and save resources. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0042] Example 1
[0043] This embodiment provides a method for preparing a sample of a cobalt-iron-boron alloy, the method comprising the following steps:
[0044] (1) In a fume hood, the cobalt-iron-boron alloy material is machined to obtain a block of cobalt-iron-boron alloy sample with a size of 20 mm×20 mm×10 mm.
[0045] (2) A nitric acid stock solution, a hydrofluoric acid stock solution and deionized water are mixed at a volume ratio of 1:1:4 to obtain a first composite acid, wherein the mass concentrations of nitric acid and hydrofluoric acid in the first composite acid are both 16.67%; a nitric acid stock solution, a hydrofluoric acid stock solution and deionized water are mixed at a volume ratio of 1:1:6 to obtain a second composite acid, wherein the mass concentrations of nitric acid and hydrofluoric acid in the second composite acid are both 12.5%.
[0046] (3) The bulk cobalt-iron-boron alloy sample was placed in a polytetrafluoroethylene cup, and then the first composite acid was added at a solid-liquid ratio of 1 g: 3 mL. The cup was then placed in an ultrasonic cleaning machine for a first pickling for 2 min at an ultrasonic power of 150 W. After the first pickling was completed, the sample was rinsed with deionized water. The sample was then placed in a polytetrafluoroethylene cup, and then the second composite acid was added at a solid-liquid ratio of 1 g: 3 mL. The cup was then placed in an ultrasonic cleaning machine for a second pickling for 2 min at an ultrasonic power of 150 W. After the second pickling was completed, the sample was rinsed with deionized water, and then rinsed with anhydrous ethanol, and dried with a baking lamp to obtain a sample to be tested.
[0047] This embodiment also provides a method for analyzing and testing cobalt-iron-boron alloy, comprising the following steps:
[0048] The sample prepared by the above method was placed in the sample chamber of the Nu Astrum glow discharge mass spectrometer and then evacuated to 10 -2 Pa, and then pushed into the discharge chamber of the glow discharge mass spectrometer; the sample was fully cooled for 10 minutes, and then sputtering was turned on, where the sputtering voltage was 1-1.1 kV, the current was 2.0 mA, and the instrument resolution was 4000-5000. After sputtering for about two hours, the test results were obtained.
[0049] Example 2
[0050] This embodiment provides a method for preparing a sample of a cobalt-iron-boron alloy, the method comprising the following steps:
[0051] (1) In a fume hood, the cobalt-iron-boron alloy material is machined to obtain a block of cobalt-iron-boron alloy sample with a size of 20 mm×20 mm×10 mm.
[0052] (2) A nitric acid stock solution, a hydrofluoric acid stock solution and deionized water are mixed at a volume ratio of 1:1:4 to obtain a first composite acid, wherein the mass concentrations of nitric acid and hydrofluoric acid in the first composite acid are both 16.67%; a nitric acid stock solution, a hydrofluoric acid stock solution and deionized water are mixed at a volume ratio of 1:1:6 to obtain a second composite acid, wherein the mass concentrations of nitric acid and hydrofluoric acid in the second composite acid are both 12.5%; a nitric acid stock solution, a hydrofluoric acid stock solution and deionized water are mixed at a volume ratio of 1:1:8 to obtain a third composite acid, wherein the mass concentrations of nitric acid and hydrofluoric acid in the third composite acid are both 10%.
[0053] (3) Place the bulk cobalt-iron-boron alloy sample in a polytetrafluoroethylene cup, then add the first composite acid at a solid-liquid ratio of 1 g: 3 mL, then place the cup in an ultrasonic cleaning machine for a first pickling for 2 min at an ultrasonic power of 150 W; after the first pickling is completed, rinse the sample with deionized water; then place the sample in a polytetrafluoroethylene cup, then add the second composite acid at a solid-liquid ratio of 1 g: 3 mL, then place the cup in an ultrasonic cleaning machine for a second pickling for 3 min at an ultrasonic power of 150 W; after the second pickling is completed, rinse the sample with deionized water; then place the sample in a polytetrafluoroethylene cup, then add the third composite acid at a solid-liquid ratio of 1 g: 3 mL, then place the cup in an ultrasonic cleaning machine for a third pickling for 5 min at an ultrasonic power of 150 W; after the third pickling is completed, rinse the sample with deionized water, then rinse the sample with anhydrous ethanol, and dry it with a baking lamp to obtain a sample to be tested.
[0054] This embodiment also provides a method for analyzing and testing cobalt-iron-boron alloy, comprising the following steps:
[0055] The sample prepared by the above method was placed in the sample chamber of the Nu Astrum glow discharge mass spectrometer and then evacuated to 10 -2 Pa, and then pushed into the discharge chamber of the glow discharge mass spectrometer; the sample was fully cooled for 10 minutes, and then sputtering was turned on, where the sputtering voltage was 1-1.1 kV, the current was 2.0 mA, and the instrument resolution was 4000-5000. After sputtering for about two hours, the test results were obtained.
[0056] It can be seen from Examples 1-2 that the sample preparation method of the present invention can effectively remove pollutants on the surface of the cobalt-iron-boron alloy and avoid the introduction of impurities as much as possible, thereby obtaining a clean sample to be tested; a glow discharge mass spectrometer is used to analyze and test the sample to be tested, the required test time is short, the test results obtained are highly accurate, and the purity analysis and impurity element analysis of the cobalt-iron-boron alloy are successfully carried out.
[0057] Example 3
[0058] The difference between this embodiment and embodiment 1 is that the mass concentrations of nitric acid and hydrofluoric acid in the first composite acid are both adjusted to 12.5%; and the mass concentrations of nitric acid and hydrofluoric acid in the second composite acid are both adjusted to 9%.
[0059] The remaining steps and parameters remain the same as those in Example 1.
[0060] Example 4
[0061] The difference between this embodiment and embodiment 1 is that the mass concentrations of nitric acid and hydrofluoric acid in the first composite acid are both adjusted to 21%; and the mass concentrations of nitric acid and hydrofluoric acid in the second composite acid are both adjusted to 16.67%.
[0062] The remaining steps and parameters remain the same as those in Example 1.
[0063] It can be seen from Example 1 and Examples 3-4 that during the sample preparation process, if the mass concentration of nitric acid and hydrofluoric acid is too low, the sample surface will not be cleaned cleanly, more impurity elements will remain, and it will take longer for the data results to stabilize; if the mass concentration of nitric acid and hydrofluoric acid is too high, the sample will be over-cleaned, and the main component elements will require a longer test time to stabilize.
[0064] Comparative Example 1
[0065] The difference between this comparative example and Example 1 is that the second composite acid and the secondary acid washing are omitted.
[0066] The remaining steps and parameters remain the same as those in Example 1.
[0067] It can be seen from Example 1 and Comparative Example 1 that, in the sample preparation process, if only one acid wash is performed, the surface cleanliness of the obtained sample to be tested is slightly low, which will lead to a longer test time of the glow discharge mass spectrometer.
[0068] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a cobalt-iron-boron alloy, characterized in that: The sample preparation method comprises: The cobalt-iron-boron alloy is pickled at least twice, and then cleaned and dried to obtain a sample to be tested; Among them, as the number of pickling times increases, the concentration of the pickling agent gradually decreases.
2. The sample preparation method according to claim 1, characterized in that: The cobalt-iron-boron alloy is in block shape with a size of 20-35 mm×20-35 mm×10-20 mm.
3. The sample preparation method according to claim 1 or 2, characterized in that: The solid-to-liquid ratio of the cobalt-iron-boron alloy and the pickling agent is 1 g:(3-5) mL.
4. The sample preparation method according to any one of claims 1 to 3, characterized in that: The pickling agent used in each pickling is a composite acid, which includes nitric acid and hydrofluoric acid; Preferably, the mass concentration of nitric acid in the composite acid is 10-20%; the mass concentration of hydrofluoric acid in the composite acid is 10-20%; Preferably, the mass concentration ratio of nitric acid to hydrofluoric acid in the composite acid is (1-3):(1-3); Preferably, as the number of pickling times increases, the mass concentrations of nitric acid and hydrofluoric acid in the composite acid gradually decrease.
5. The sample preparation method according to any one of claims 1 to 4, characterized in that: The time range of each pickling is 2-5min.
6. The sample preparation method according to any one of claims 1 to 5, characterized in that: Each pickling process is accompanied by ultrasound, and the power range of the ultrasound is 120-180W.
7. The sample preparation method according to any one of claims 1 to 6, characterized in that: In the process of at least two picklings, a water washing step is performed between two adjacent picklings; Preferably, the cleaning comprises the steps of sequentially performing water washing and alcohol washing; Preferably, a baking lamp is used to dry the material after alcohol washing.
8. A method for analyzing and testing cobalt-iron-boron alloy, characterized in that: The analytical testing method comprises: The sample to be tested prepared by the sample preparation method according to any one of claims 1 to 7 is placed in a glow discharge mass spectrometer, and then cooled and sputtered in sequence to obtain a test result.
9. The analysis and testing method according to claim 8, characterized in that: The sputtering voltage is 1-1.1 kV.
10. The analytical testing method according to claim 8 or 9, characterized in that: The sputtering current is 2-2.2 mA; Preferably, the resolution of the glow discharge mass spectrometer is 4000-5000.
Citation Information
Patent Citations
Method for detecting content of trace impurity content in metal by glow-discharge mass spectrometry
CN106198712A
Preparation method of ultra-high purity aluminum sample for GDMS detection and impurity analysis method of ultra-high purity aluminum sample
CN107843478A
Ferro-molybdenum sample and preparation method thereof, and method for determining content of components in ferro-molybdenum alloy
CN112051290A
Mixed acid for dissolving molybdenum-niobium alloy sample and preparation method and application thereof
CN112229833A
Method for detecting content of impurity elements in cobalt
CN113049671A